2006
DOI: 10.1021/ie060484t
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Oxide Catalysts Supported on TiO2, Al2O3, and SiO2:  A Comparison for Low-Temperature SCR of NO with NH3

Abstract: A series of TiO2-, Al2O3-, and SiO2-supported manganese oxide catalysts were prepared, characterized, and catalytically tested for selective catalytic reduction (SCR) of NO with NH3 in the presence of excess oxygen at low temperatures (373−523 K). Various commercial supports were used in this study to find out the influence of surface area, support nature (acidic, basic), and crystalline phase on SCR activity. XRD studies reveal the presence of anatase and rutile phases for titania supports and the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(118 citation statements)
references
References 25 publications
5
112
0
1
Order By: Relevance
“…However, it is thought that the catalysts calcined at temperatures over 600 C plugged the micropores of the support materials and either sintered or agglomerated as crystallite Mn 2 O 3 because of the thermal effect. These results are in agreement with previous studies (Peña et al, 2004;Smirniotis et al, 2006).…”
Section: Characterization Of Catalystssupporting
confidence: 94%
“…However, it is thought that the catalysts calcined at temperatures over 600 C plugged the micropores of the support materials and either sintered or agglomerated as crystallite Mn 2 O 3 because of the thermal effect. These results are in agreement with previous studies (Peña et al, 2004;Smirniotis et al, 2006).…”
Section: Characterization Of Catalystssupporting
confidence: 94%
“…The enhanced NO conversion at a relatively higher temperature using Mn-based catalyst has been reported [34][35][36][37]. Similar results were also found while using other catalysts (Figures 3 and 4).…”
Section: Comparison Of Co 2 and N 2 Atmosphere With Different Catalystssupporting
confidence: 87%
“…Manganese oxides usually show good SCR activity in the low temperature range, such as pure MnO x [7,8], MnO x loaded on TiO 2 / Al 2 O 3 /SiO 2 /AC (activated carbon) [9][10][11][12] and Mn-Ce, Mn-Cu mixed oxides [13][14][15]. Previous studies showed that in Fecontaining SCR catalysts, the introduction of Mn could obviously enhance the low temperature activity [16,17], probably due to the synergistic effect between iron and manganese species.…”
Section: Introductionmentioning
confidence: 99%